Zakat Profesi Perspektif Hukum Islam: (Suatu Kajian Pendekatan Maqashid Syari’ah) - Muhazir (Islamic Circle, 2021)
The problem of zakat is still a phenomenon that will always exist along with the times. Of course, as a Muslim community, we understand that zakat is one of the pillars of Islam that must be fulfilled as explained in the Qur'an and al-Hadith. Professional zakat is still being debated, this is because there is no evidence in the Qur'an and Hadith that implicitly confirms professional zakat. This paper is the result of library research with a maqashid sharia approach. The results of the study show that professional zakat when viewed from the maqashid sharia aspect contains many benefits both in terms of maintaining a property, life, and religion. Not only that, even professional zakat can be used to help the community's economy in meeting the needs of life if it is managed properly and is not only consumptive.